The physical and physiological demands of small-sided games: How important is winning or losing? - Malone, S.; Collins, K. (International Journal of Performance Analysis in Sport, 2016)
The present study examined the effect that success (win) or failure (loss) during competitive small-sided games (SSG) has on physical and physiological demands. Twenty six outfield hurling players were monitored with GPS (4-Hz, VX Sport, New Zealand) and heart rate monitors (Polar Electro, Oy, Kempele, Finland). Total distance (m), high-speed distance (= 17 km·h-1; m), sprint distance (= 22 km·h-1; m) and peak velocities (km·h-1) during SSG were analysed. Time spent in different HR zones, maximum heart rate (HRmax), average HR and percentage of HRmax were also considered. Results showed significant effects for team success (win) on all collected variables, with successful teams showing significantly higher total distances (p = 0.013; d = 3.50 ± 0.30; very large) when compared to losing teams. Team success during SSG impacted high-speed performance with winning teams covering more distance (p = 0.002; d = 4.53 ± 0.46; very large). Similar trends were documented for physiological variables with significant effects reported for winning teams spending more time at higher percentages (=95%) of HRmax when compared to losing teams (p = 0.013; d = 2.64 ± 0.34, very large). The current study has shown that success (win) or failure (loss) within SSG plays an important role for SSG design.